MASA DEPAN SERIKAT PEKERJA DI ERA OTOMATISASI DAN AWAL ARTIFICIAL INTELLIGENCE DI INDONESIA - Risky Rofiansyah; Muhammad Zufar Juhaidi; Mohammad Aminollah; Miftahul Rasikin; Sentot Imam Wahyono (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this article is to discuss two significant upcoming challenges that unions will face in Indonesia. The first is the role of trade unions in the transition from a labor economy to an automation economy. This is achieved through the integration of two research methodologies – intuitive logic, which is a branch of scenario planning, and a rigorous literature review of the contextual environment in times of disruption and change. It seems that automation and AI must have had a huge impact on the human workforce because before citizen automation existed. Indonesia already has a lot of jobs/unemployment, so logically if automation and AI develop rapidly in Indonesia, of course there will be a reduction in the human workforce because they are replaced by machines or robots.. Mass production industries are clearly most likely to be automated, and their workers are more likely to be replaced by AI-driven industrial robots. Unions in transition to an unemployment economy are likely to negotiate with governments as well as companies in order to defend the rights of Indonesian workers.